Biochemical analysis of arginase and ornithine carbamoyltransferase in human vitreous humor - Gürsu, MF (Elsevier Science Inc, 2001)
Background. The presence of arginase and ornithine carbamoyltransferase (OTC'ase) enzymes in human vitreous humor after death was investigated in this study. To the best of our knowledge, there is no prior report on the activity of arginase or ornithine carbamoyltransferase in human vitreous humor. Methods. The presence of arginase and OTC'ase activities were examined in the human vitreous humor of 19 samples. Spectrophotometric methods were used to determine activities of arginase and OTC'ase. Results. Arginase activity was detected in human vitreous humor, whereas OTC'ase activity was below the detection limit. Therefore, we focused on biochemical analysis of arginase in human vitreous humor. Kinetic properties of arginase activity in vitreous humor were optimized. In contrast to other arginases, optimal preincubation temperature and pH were 40 degreesC and 8.8, respectively. Km of vitreous arginase for L-arginine was 6 mm. Preincubation of the enzyme with Mn2+ ions caused a significant increase (33%) in arginase activity. Conclusions. The activity and presence of arginase as well as its kinetics in human vitreous are documented in this study. Biochemical functions and the importance of arginase in vitreous humor are not well understood. However. its presence may be explained by means of its involvement in polyamine biosynthesis as observed in the other extrahepatic tissues. (C) 2001 IMSS. Published by Elsevier Science Inc.
Keywords: human vitreous humor; arginase; ornithine carbamoyltransferase; enzyme kinetics